PRODUK PEMBIAYAAN PINJAM SAMBIL SIMPAN UANG (PISANG) BPRS BAHARI BERKESAN KOTA TERNATE: UPAYA PENINGKATAN EKONOMI UMMAT - Risdan Harly; Syaifuddin Syaifuddin (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2021)
The purpose of the research is to find out and analyze, how the application of mudharabah agreements in the financing of Borrow While Saving Money (PISANG) at PT. PBRS Bahari Berkesan Kota Ternate, to find out and analyze, how the Role of Borrowing Products While Saving Money (PISANG) to empower efforts to improve the economy of the ummah. The research method used is a type of descriptive qualitative research. The results of the study showed the implementation of mudharabah agreements with the financing of Loan While Saving Money (PISANG) products by Bank BPRS Bahari Berkesan in Ternate City, running optimally because, many communities have been successful to improve their economies both short, medium and long term and banks are able to provide an understanding of the Islamic economic system in using Mudharabah agreements with profit sharing systems between banks and customers.